The From-Tayloristic-to-Holistic-Organization Model From an Empirical Perspective - Vivian Carstensen (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2002)
The objective of the paper is to confront the conclusions in the seminal papers of Lindbeck and Snower (2001, 2000, 1996) and Snower (1998) with the empirical evidence in the manufacturing sector, thus testing the from-Tayloristic-to-holistic-organization model. Starting from stylized facts as growing incidence of so called high performance/high involvement work systems, the major theoretical findings on determinants and effects of complementary systems of work organization are recapitulated. The derived hypotheses to be tested are: The coexistence of two distinct types of work organization can be shown. According to their characteristics, these types describe a rank order with respect to the existence of sophisticated instruments of human resource management policy. Due to the complementarity property, we observe increasing productivity effects of team production, thus being larger in holistic firms. Empirical evidence reveals that still 43% of firms have a Tayloristic work organization. Holistic firms are more productive. Marginal returns from reorganization towards multiple tasks (team work) prove to be negative in Tayloristic firms and to be positive in holistic firms. Although only borderline significant, these results can be interpreted as an indication for the complementarity hypotheses stipulated by Lindbeck and Snower.
Keywords: D24; J24; L23; M11; M12; 330; Arbeitsorganisation; Organisatorischer Wandel; Lernprozess; Informationstechnik; Humankapital; Schätzung; Deutschland